Do estado de "armário" para “problema público”: análise sobre o processo de aquisição de visibilidade estatística da população LGBT no Sistema Único de Assistência Social de Belo Horizonte/MG – SUAS-BH - Walkiria Glanert Mazetto (2023)
This work aims to demonstrate how the LGBT population has, to some extent, moved from the "Closeted State" to becoming a "Public Issue" through a long historical process of gaining visibility in public databases. The analysis universe chosen was the Municipal Social Assistance Policy of the City Hall of Belo Horizonte - PBH, which is part of the National Unified Social Assistance System - SUAS, known as SUAS-BH. This choice was made because this policy already includes fields for sexual orientation and gender identity in the main official database, called the Social Programs Information and Management System - SIGPS. However, these fields are not mandatory for filling out by public officials and have a filling rate of only 1% in relation to the overall number of registrations. It is assumed that the statistical visibility of the LGBT population in SUAS-BH today is the result of a historical process of constituting a public and institutional agenda inherent to the culture of public issues. The research objective was to understand the process of acquiring statistical visibility of the LGBT population in SUAS-BH. Therefore, the aim was to analyze which policies, agencies, and services (governmental and non-governmental) have been or are involved in this process, how they relate to each other, what potential areas of conflict exist, and how tensions arise and are (or are not) resolved. The methodology used was qualitative, through documentary research and semi-structured interviews. Additionally, participant observation was employed, considering the author's professional immersion, which provided an empirical focus for the scientific investigation. The documentary research aimed to investigate various institutional documents of SUAS-BH, allowing a comparison between the official governmental discourse, the statistical data found, and the opinions of the 29 public officials interviewed. The material was treated through content analysis. The research results indicated that the process of LGBT statistical visibility in SUAS-BH is expressed in three general aspects: 1) Historical aspects: this process of LGBT agenda formation was demonstrated, showing how it intersected late in SUAS-BH compared to other public policies. Progress has been made, and this segment is now identified as a priority public in SUAS-BH norms. However, two aspects that pose barriers and difficulties were identified: 2) Structural aspects: operational difficulties regarding databases, technical qualifications and specific norms, relations between the state and the third sector, statistical instrumentalization, and social assistance surveillance; and 3) Symbolic or cultural aspects: individual attitudes, opinions, stigmas, religious issues, ethical and moral values, political and ideological conceptions, lifestyles, generational issues, etc. In conclusion, the existing statistical visibility of the LGBT population in SUAS-BH today is the result of a historical process of constituting a public and institutional agenda inherent to the culture of public issues, which has advanced through the pressure of past LGBT social activism, transforming it from a "state of affairs" into a public problem. However, this process has encountered structural and symbolic aspects of the state's dynamics that indicate that LGBT statistical visibility is a field of power dispute in the political arena.